A model of human immunodeficiency virus encephalitis in scid mice. - Tyor, W R (1993)
Human immunodeficiency virus (HIV)-associated dementia complex is a common and devastating manifestation of the late phases of HIV infection. The pathogenesis of dementia complex is poorly understood and effective treatments have not been developed, in part because of the lack of an appropriate animal model. Mice with severe combined immunodeficiency (scid mice), which accept xenografts without rejection, were intracerebrally inoculated with human peripheral blood mononuclear cells and HIV. One to 4 weeks after inoculation, the brains of these mice contained human macrophages (some of which were HIV p24 antigen positive), occasional multinucleated cells, and striking gliosis by immunocytochemical staining. Human macrophages also were frequently positive for tumor necrosis factor type alpha and occasionally for interleukin 1 and VLA-4. Cultures of these brains for HIV were positive. Generally, human macrophages were not present in the brains of control mice, nor was significant gliosis, and HIV was not recovered from mice that received HIV only intracerebrally. Pathologically, this model of HIV encephalitis in scid mice resembles HIV encephalitis in humans and the data suggest that the activation of macrophages by infection with HIV results in their accumulation and persistence in brain and in the development of gliosis. This model of HIV encephalitis should provide insights into the pathogenesis and treatment of this disorder.